If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -3 = y Reorder the terms: -3 + x = y Solving -3 + x = y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + x = 3 + y Combine like terms: -3 + 3 = 0 0 + x = 3 + y x = 3 + y Simplifying x = 3 + y
| 96-5x=7x+54 | | 19x^2+19x+12=0 | | -6w=-8 | | x^2=4x+4+100 | | 4y=256 | | 3y-1=(10y-18)/2 | | (3y-1)/2=(10-18) | | (3y-1)=2(10-18) | | 2(3y-1)=10-18 | | (8x-3)=3(5x+6) | | 3(8x-3)=5x+6 | | 8k-6k+3k= | | x+(x-6)=32 | | 32*2=64 | | ln(x-2)+ln(2x+1)=5 | | b(b-6)=27 | | 3a^2b+2a^2b^2=ab^2+a^2b^2 | | b^2=5b | | 11x+8=129 | | b^2=-30-11b | | (t+3)(t-6)=0 | | a+7= | | 27p+17q+p-7q-5p= | | 48x=6x | | (55)*7= | | (55)7= | | 7m+3n-2m+9n= | | (5/2)7= | | 3x+5-(2)3=20 | | x^2=0.25 | | 70(x-4)=50x | | x^2-29x-168=0 |